Role of Wild Food Environments for Cultural Identity, Food Security, and Dietary Quality in a Rural American State - Ahmed, Selena; Warne, Teresa; Stewart, Alyssa; Byker Shanks, Carmen; Dupuis, Virgil (Frontiers in Sustainable Food Systems, 2022)
Wild foods are primary components of traditional and Indigenous food systems that are valued for food security while being vulnerable to global change. This case study examines practices, experiences, and perceptions associated with wild food environments through a household survey in the rural American state of Montana. Findings highlight that wild food environments contribute to cultural identity, sense of place, food security, and dietary quality of surveyed households while being vulnerable to loss of traditional ecological knowledge as well as climate and land-use change. Of the 182 informants, 80% hunt, 83% fish, and 68% forage wild botanicals. More than half of the informants agreed that wild food procurement is part of their cultural identity (66%). Collectively, informants procure more than 172 wild food species with the most prevalent being deer, waterfowl, elk, trout, bass, a range of berries, mushrooms, and botanicals used medicinally. Participants have a multidimensional value system where wild food procurement is valued for diets, recreation, family time, spirituality, and connection to the environment. The majority of participants agreed that the consumption of wild foods contributes to the nutritional quality (87%) and diversity (82%) of their diets while lowering food costs (59%). At least half of the informants reported observing changes in climate patterns over the past decade including increased temperature (50%) and more extreme and variable weather patterns (38%) that they perceive are impacting wild food environments including shifts in wild game, fish, and edible plant populations. Based on findings, we support that wild food environments and associated bio-cultural resources are a critical place to understand, conserve, and promote for nutrition. We thus advance the concept of ‘conservation for nutrition’. Community engagement, education, and policy plans are called for to promote wild food environments towards supporting sustainable diets and planetary health.